2015
DOI: 10.15252/emmm.201505439
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant epigenome in iPSC ‐derived dopaminergic neurons from Parkinson's disease patients

Abstract: The epigenomic landscape of Parkinson's disease (PD) remains unknown. We performed a genomewide DNA methylation and a transcriptome studies in induced pluripotent stem cell (iPSC)‐derived dopaminergic neurons (DAn) generated by cell reprogramming of somatic skin cells from patients with monogenic LRRK2‐associated PD (L2PD) or sporadic PD (sPD), and healthy subjects. We observed extensive DNA methylation changes in PD DAn, and of RNA expression, which were common in L2PD and sPD. No significant methylation diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
128
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 77 publications
(142 reference statements)
10
128
0
1
Order By: Relevance
“…Another study observed methylation alterations in sporadic PD iPSC-derived dopaminergic neurons [87], which was the first to describe epigenetic dysregulation in the disease.…”
Section: Sporadic Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study observed methylation alterations in sporadic PD iPSC-derived dopaminergic neurons [87], which was the first to describe epigenetic dysregulation in the disease.…”
Section: Sporadic Pdmentioning
confidence: 99%
“…One study found increased mitochondrial DNA damage in neural cells from patients, which was reversed when the mutation was genetically corrected [25]. Similar to sporadic PD iPSCderived dopaminergic neurons, it has been shown that epigenetic dysregulation also occurs in LRRK2-associated PD patients [87]. Interestingly, the commonly described Lewy body pathology has yet to be observed in the iPSC-derived neurons.…”
mentioning
confidence: 99%
“…Together with the lack of longitudinal studies in human samples that would allow to establish the disorder-causality role of the epigenetic alterations observed, it is clear that the need of better ‘humanized' dynamic models of the pathologies could improve our understanding of dementia. Research with induced pluripotent stem cells differentiated to specific neuronal populations 174 or single-cell epigenomics 175 will undoubtedly reveal a completely new level of complexity and a set of genes that are altered in dementia-associated pathologies by identifying causal associations between neuronal dysfunctions, gene expression and epigenetic (de)regulation. Recent advances in genetic and epigenetic editing through technologies such CRISPR/Cas9 176, 177 will undoubtfully provide a powerful experimental tool that will allow to validate epigenetically altered targets to improve the possible causality of DNA methylome alteration in dementia.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…These differences might be attributable in part to sample size, but Fernandez-Santiago et al ,. have shown differential methylation profiles in different cell types from PD patients [27]. They derived dopaminergic neurons from induced pluripotent stem cells (iPSCs) of PD patients and healthy controls.…”
Section: Epigenetics and The Genome: Dna Methylationmentioning
confidence: 99%